MARKETING COMMUNICATION STRATEGY PT. GO-JEK INDONESIA IN INCREASING THE NUMBER OF CONSUMERS - Lisdiantini, Netty; Siska Armawati Sufa; Bindara, Farah Zain Putri; Rohman, Suhudi Rohman; Pradana , Asya Pradana R (Journal of International Multidisciplinary Research, 2024)
This study investigates the dynamic marketing and communication strategies used by PT. Gojek Indonesia to strengthen its consumer base. As one of Southeast Asia's leading technology-based platforms, Gojek has rapidly expanded its services beyond ride-hailing to include food delivery, digital payments, and more. This research uses a qualitative approach, combining interviews, case studies, and industry analysis to dissect the multifaceted strategy implemented by Gojek. This study explores Gojek's proficient use of digital channels and social media to drive consumer engagement. By analyzing consumer behavior and preferences, the study explains how Gojek tailors its marketing messages to resonate with diverse target audiences. In addition, this study examines the role of strategic partnerships and collaborations in strengthening Gojek's market presence and attracting new consumers. Furthermore, the study explores the impact of innovative features and services introduced by Gojek, such as loyalty programs and seamless user interfaces, on customer acquisition and retention. The study identifies the critical role of data analytics in shaping personalized marketing campaigns that appeal to specific consumer segments. The findings from this study contribute to a broader understanding of effective marketing and communication strategies in technology-based service industries. The insights derived from Gojek's approach provide valuable lessons for businesses looking to navigate a competitive market and expand their consumer base through strategic marketing initiatives.